Research progress and development trend in polymer based on myrcene - "WANG Qin-fang1, QIU Bo2, TANG Hai-kun1, DONG Jing1, LI Wei-tian1, LI Fu-chong1, REN Hai-ou1, ZHAO Jian-ping1 " (Hecheng xiangjiao gongye, 2023)
Myrcene, as a kind of conjugated diene from plants, its unique side chain and double bond structure on side chain provided a new way for the synthesis of new materials. This article introduced the research progress of homopolymerization and co-polymerization of myrcene with other monomers, as well as the application of myrcene in preparation of new materials, and prospected its development trend with 25 references.